Efficacy and safety of a 4-year combination therapy of growth hormone and gonadotropin-releasing hormone analogue in pubertal girls with short predicted adult height - Dotremont, Hilde; France, Annick; Heinrichs, Claudine; Tenoutasse, Sylvie; Brachet, Cécile; Cools, Martine; De Waele, Kathleen; Massa, Guy; Lebrethon, Marie-Christine; Gies, Inge; Van Besien, Jesse; Derycke, Christine; et al. (Frontiers in Endocrinology, 2023)
Objectives To improve adult height in pubertal girls with a poor height prediction, treatment with growth hormone (GH) can be used in combination with a gonadotropin releasing hormone agonist (GnRHa), to delay closure of the growth plates. However, there are few studies to support this practice, and they show conflicting results. The objective of this trial is to assess the safety and efficacy of this combination treatment in early pubertal girls with a short predicted height, in comparison with matched controls. Design, patients, and methods We designed an open-label, multicenter, interventional case-control study. Early pubertal girls with predicted adult height (PAH) below -2.5 SDS, were recruited in tertiary care centers in Belgium. They were treated for four years with GH and GnRHa. The girls were followed until adult height (AH) was reached. AH vs PAH, AH vs Height at start, and AH vs Target Height (TH) were evaluated, as well as safety parameters. Control data were assembled from historical patient files or from patients who preferred not to participate in the study. Results Sixteen girls with mean age ( ± SD) at start of 11.0 years (± 1.3) completed the study protocol and follow-up. Their mean height ( ± SD) increased from 131.3 ± 4.1 cm (-2.3 ± 0.7 SDS) at start of treatment to 159.8 ± 4.7 cm (-1.1 ± 0.7 SDS) at AH. In matched controls, height increased from 132.3 ± 4.2 cm (-2.4 ± 0.5 SDS) to 153.2 ± 3.4 cm (-2.1 ± 0.6 SDS) (p<0.001). AH surpassed initial PAH by 12.0 ± 2.6 cm in treated girls; and by 4.2 ± 3.6 cm in the controls (p<0.001). Most treated girls reached normal adult height (>-2SD) (87.5%) and 68.7% reached or superseded the target height (TH), which was the case in only a minority of the controls (37.5% and 6.2%, respectively) (p= 0.003 and 0.001). A serious adverse event possibly related to the treatment, was a fracture of the metatarsals. Conclusion A four-year GH/GnRHa treatment in early pubertal girls with a poor PAH seems safe and results in a clinically relevant and statistically significant increase in AH compared with matched historical controls. Clinical trial registration ClinicalTrials.gov, identifier NCT00840944.